Pembelajaran Berbasis Permainan Digital dalam Pendidikan: Analisis Bibliometrik terhadap Tren Penelitian, Jenis Permainan Digital, dan Fokus Tematik pada Keterlibatan Peserta Didik. - Dewi Nor Wahyuni; Heni Purwa Pamungkas; Albrian Fiky Prakoso (CV. Pusdikra Mitra Jaya, 2026)
Advances in digital technology have brought about significant changes in the world of education, one of which is the implementation of Digital Game-Based Learning (DGBL), which is believed to enhance student engagement. However, research on on DGBL still shows a diversity of focus, both in terms of publication trends, fields of study, and the types of games used. This study aims to map the development of DGBL research in relation to student engagement using a bibliometric approach. The research method consists of a bibliometric analysis using data drawn from the Scopus database for the period 2017-2026. Articles were systematically selected until 50 publications meeting the inclusion criteria were obtained. Data analysis utilized the Biblioshiny software to identify publication trends, the distribution of scientific fields, and the dominant types of games. The results indicate an increase in DGBL publications with an annual growth rate of 16.65%. The study was dominated by the sciences (74%), particularly health, engineering, and biology, while the social sciences accounted for only 26%, with a focus on business, education, and literacy. In terms of game types, serious games ranked first (54%), followed by quiz games, simulation games, role-playing games, and augmented reality. These findings underscore the significant potential of DGBL in enhancing learning engagement; however, its application remains concentrated in the sciences, necessitating broader development in the social sciences.